Modelagem e jogos avaliativos como ferramentas para o aprendizado do efeito fotoelétrico em situações do cotidiano dos alunos - Oliveira, Soetânia Santos de (2024)
The main objective of this research is to analyze how the use of modeling and games can contribute to the learning of the photoelectric effect in high school in everyday situations. It brings as a scientific contribution a proposal of a Potentially Significant Teaching Unit that aims to make physics classes more dynamic and attractive to students. The research is based on David Ausubel’s significant learning, since for its effective development steps were fulfilled that involve the use of students’ previous knowledge to consolidate scientific knowledge and potentially significant didactic material. The didactic sequence was developed over four classes, in which the content was worked with the realization of simulations using the PhET platform, the exhibition of a video about EFE, and the use of educational games. Data collection was carried out in two moments, in the first and last classes, with the application of evaluative game, and the data treatment was carried out through the comparative analysis of the initial and final results obtained. This analysis revealed that there was an increase in the students’ performance after applying the didactic sequence, which can be interpreted as an effectiveness or result of significant learning. In addition, approximately 90% of students approved the methodology used. In this way, it is argued that the applied PSTU is effective to teach the Photoelectric Effect and its applications in the new high school, and as such, it is expected to contribute to improve the teaching-learning process of Physics.